Genomic dissection of the antimicrobial resistance epidemiology of Salmonella Typhimurium - Kaur, Sandeep; Partridge, Sally R.; Payne, Michael; Sintchenko, Vitali; Lan, Ruiting (Frontiers in Microbiology, 2025)
IntroductionSalmonella Typhimurium (STm) is a globally distributed foodborne pathogen showing increasing antimicrobial resistance (AMR), particularly to fluoroquinolones and third-generation cephalosporins. Multiple countries have implemented ongoing genomic surveillance programs for Salmonella, but comprehensive global analyses integrating genomic typing and AMR in STm remain scarce.MethodsPublicly available genomes of ~65,000 STm isolates were characterized using Multilevel Genome Typing (MGT). Resistance was predicted to 14 clinically-relevant antibiotics. Resistance patterns were analyzed by MGT sequence type (ST), geographic location, year of collection, and source. MGT ST where ≥80% isolates were predicted to be resistant to an antibiotic were defined as a resistant ST for that antibiotic.ResultsAbout half of all STm isolates were predicted to be resistant to ≥1 antibiotic. Resistance frequencies varied substantially by country, collection year and MGT ST, and 407 resistant MGT STs were identified. Among the most recent isolates (2021–2022), eight MGT STs were classified as cefotaxime resistant and three as ciprofloxacin intermediate. Cefotaxime resistant MGT STs predominantly included isolates from cattle/poultry in the USA. Ciprofloxacin intermediate MGT STs were mainly linked to swine from the UK.DiscussionThis large-scale genomic analysis highlights substantial diversity in AMR patterns among STm genomic types globally. The identification of recently emerged cefotaxime resistant and ciprofloxacin intermediate STs underscores the continued threat of resistance to antibiotics critical for treatment of severe salmonellosis. Integration of MGT strain typing with AMR prediction provides scalable, sharable, standardised and precise tracking of resistant isolates/STs, offering a powerful framework for global AMR surveillance.